Ectopic Pancreas in the Gastric Antrum Wall Complicated by Ectopic Pancreatitis and Persistent Gastric Abscess. Issue 1 (2018) - Alastal, Yaseen; Khalil, Basmah; Singh, Surendra; Almadani, Sameh B.
ABSTRACT : N/A: Ectopic pancreas is an uncommon finding in the stomach. Complications are rare but can lead to significant morbidity and even mortality. We report a 49‐year‐old man who presented with upper abdominal pain, vomiting, and weight loss and was found to have a gastric wall abscess that developed a few weeks after endoscopic biopsy of a gastric ulcer. After medical treatment failed to resolve his symptoms, he underwent distal gastrectomy with Roux‐en‐Y gastrojejunostomy. Postoperatively, the gastric wall abscess was determined to have derived from a focus of ectopic pancreatic tissue with evidence of ectopic chronic pancreatitis.